FAKTOR PENYEBAB KECEMASAN ISTRI MENGHADAPI SUAMI YANG DIRAWAT INAP DI RSUD DR. PIRNGADI MEDAN - Rudi Marhujar; Badiran -; Jamaluddin - (Fakultas Kesehatan Masyarakat Universitas Prima Indonesia, 2020)
ABSTRACT Anxiety is a normal reaction to situations that are very stressful in a person's life. Anxiety can appear alone or combine with other symptoms of various emotional disorders. The purpose of this study was to analyze the factors that cause the wife's anxiety to face her husband who was hospitalized at Dr. Pirngadi Medan in 2020 This type of research is an analytic survey with a cross sectional study design. The study was conducted inpatient at Dr. RSUD Pirngadi Medan. There were 88 research samples which were obtained using the Slovin formula. To analyze the data logistic regression test was used. Based on the results of the study note that the cost of treatment, factors at risk of losing loved ones, healing factors, factors that take care, household factors, family life threat factors, and length of stay factors affect the anxiety of the wife facing her husband who was hospitalized in hospitals DR. Pirngadi Medan 2020 and the most related factor is the risk of losing a loved one. Based on the results of the study, it is suggested that wives can increase their faith so that they can be patient in facing husbands who are hospitalized and can increase their trust or confidence in hospital services for the healing of hospitalized husbands.